2019
DOI: 10.5194/tc-2019-168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incorporating moisture content in surface energy balance modeling of a debris-covered glacier

Abstract: Abstract. Few surface energy balance models for debris-covered glaciers account for the presence of moisture in the debris, which invariably affects the debris layer's thermal properties and, in turn, the surface energy balance and sub-debris melt of a debris-covered glacier. We adapted the Interactions between Soil, Biosphere, and Atmosphere (ISBA) land surface model within the SURFace EXternalisée (SURFEX) platform to represent glacier debris rather than soil. The new ISBA-DEBris model includes the varying c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Thus, accounting for latent heat fluxes, within debris in the context of the Giese et al. (2020) model or a similar moisture content debris model is the next logical step to testing our hypotheses and advancing our understanding of heat flux in supraglacial debris. Such a model could be constrained by the data analysis and nonconductive heat flux constraints that we present in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, accounting for latent heat fluxes, within debris in the context of the Giese et al. (2020) model or a similar moisture content debris model is the next logical step to testing our hypotheses and advancing our understanding of heat flux in supraglacial debris. Such a model could be constrained by the data analysis and nonconductive heat flux constraints that we present in this work.…”
Section: Discussionmentioning
confidence: 99%
“…However, these thermal properties have been found to be stable during the core monsoon months (Rowan et al, 2020), so we kept k d constant in time at each site in our model. Additional, targeted investigations should examine the possible role of water storage and mobility within debris layers (Giese et al, 2020;Collier et al, 2014).…”
Section: Limitationsmentioning
confidence: 99%
“…Ablation is often expected to be higher on such 'dirty ice glaciers' than at both clean-ice sites and at sites with established debris cover, as shown experimentally (Reznichenko et al, 2010;Östrem, 1959), and by means of modelling (Reid and Brock, 2010), with humidity being a determining factor for this enhancement (Evatt et al, 2015). Moisture in debris is an important factor under monsoonal conditions, controlling the debris' thermal properties and thus ablation (Sakai et al, 2004;Nicholson and Benn, 2006) and has been the focus of devoted modelling studies (Giese et al, 2020;Collier et al, 2014). Moreover, the representation of latent heat due to evaporation (Giese et al, 2020;Steiner et al, 2018) and atmospheric stability correction for turbulent fluxes were shown to be important to improve the simulation of sub-debris melt (Reid and Brock, 2010;Mölg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…debris thickness, moisture content, surface roughness; Fyffe et al, 2014) and the contribution of sub-glacial channels to the total melt is not understood (Benn et al, 2017). The limited understanding of basic physical properties, and the high spatial heterogeneity of these glaciers, hinders the development of accurate melt estimates by models (Collier et al, 2014;Giese et al, 2019).…”
Section: How Do Turbulent Fluxes Drive the Energy Exchange On Debris-mentioning
confidence: 99%